2005
DOI: 10.1104/pp.104.055673
|View full text |Cite
|
Sign up to set email alerts
|

Local Coexpression Domains of Two to Four Genes in the Genome of Arabidopsis

Abstract: Expression of genes in eukaryotic genomes is known to cluster, but cluster size is generally loosely defined and highly variable. We have here taken a very strict definition of cluster as sets of physically adjacent genes that are highly coexpressed and form so-called local coexpression domains. The Arabidopsis (Arabidopsis thaliana) genome was analyzed for the presence of such local coexpression domains to elucidate its functional characteristics. We used expression data sets that cover different experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
55
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 32 publications
11
55
0
Order By: Relevance
“…Compared with the expected degree of coexpression (i.e. maximum 10% with the 90th percentile PCC threshold), these genes showed no strong evidence for large-scale coregulation (Ren et al, 2005). Of all orthologous colinear gene pairs, 69% had a conserved ECC.…”
Section: Ecc Patterns For Evolutionarily Conserved Plant Genesmentioning
confidence: 82%
“…Compared with the expected degree of coexpression (i.e. maximum 10% with the 90th percentile PCC threshold), these genes showed no strong evidence for large-scale coregulation (Ren et al, 2005). Of all orthologous colinear gene pairs, 69% had a conserved ECC.…”
Section: Ecc Patterns For Evolutionarily Conserved Plant Genesmentioning
confidence: 82%
“…This proportion may be even higher if we consider that we only analyzed one-third of the putative 8,000 genes located on chromosome 3B. In particular, the hybridization-based approach cannot detect tandemly duplicated genes that have been shown to be more prone to coexpression than adjacent nontandemly duplicated genes (Williams and Bowles, 2004;Ren et al, 2005;Zhan et al, 2006). We also found a few coexpressed gene clusters that were conserved between wheat and rice or B. distachyon, suggesting that genes maintained their proximity during the evolution and that common regulatory mechanisms are also conserved between plant genomes.…”
Section: Discussion Genome Rearrangements Shaped the Wheat Genome Thrmentioning
confidence: 98%
“…In the human, mouse (Mus musculus), Arabidopsis, and rice genomes, the percentage of adjacent coexpressed genes ranges from 2% to 10% with two to four genes involved (Ren et al, 2005(Ren et al, , 2007Sémon and Duret, 2006;Zhan et al, 2006). In fruit fly, Spellman and Rubin (2002) found 20% of adjacent genes that were part of large coexpression domains involving 10 to 30 genes.…”
Section: Discussion Genome Rearrangements Shaped the Wheat Genome Thrmentioning
confidence: 99%
See 1 more Smart Citation
“…nucleosome positions) has a strong effect on gene expression, which suggests that translocated duplicates may show expression divergence by virtue of chromosomal position alone. In addition, Ren et al (2005) found that tandem duplicates that shared expression domains tended to have dissimilar sequence-based functions. Shoja et al (2007) noted that tandem gene duplicates tended to show a relationship between expression divergence and chromosomal distance.…”
Section: Properties Of Genes That Influence Duplicate Specializationmentioning
confidence: 99%